Structure of Japanese athletes' thoughts during competition and their tendencies of occurrence - Aritomi, K.; Toyama, M. (Japanese Journal of Sport Psychology, 2015)
Thought content of Japanese undergraduate athletes (N=166) during sport competitions was investigated. Participants were asked to imagine moments of superior and inferior performances from a recent competition; to recall the situation and their thought content as well as emotions in both situations; and to write down in free description. Labels of the situation, thought content, and emotions obtained during the investigation were each classified into categories. A multiple correspondence analysis revealed that thoughts and emotions depend on the quality of performance or the competition situation. A chi-square test and residual analysis of frequency in each thought category showed that thoughts of positive attitude, psychological instructions and expectations for future occurred significantly more often in moments of superior performance. In contrast, thoughts of negative attitude and worry occurred more frequently in moments of inferior performance. In addition, similar analyses were performed on a group of participants who had experienced anxiety and on a separate group who had not experienced anxiety in moments of inferior performance. As a result, significant deviation was not observed in the frequency of thoughts of worry between both groups. This finding suggests that Japanese athletes may have concerns about the possibility of poor performance and it may result in a defensive cognitive strategy, even when they do not actually feel anxiety.